Europa Postmediaevalis 2020 : post-medieval pottery in the spare time - Blažková, Gabriela, 1974-; Matějková, Kristýna (Archaeopress Publishing Ltd, 2021)
A collection of papers planned for what would have been the second Europa Postmediaevalis conference. The focus is on the Early Modern period (15th to 18th centuries) and the growing use of new ceramic forms for leisure activities (smoking, drinking coffee or alcohol, garden strolls or games).